Populism and the Fading Embedded Liberalism? - Muhammad Sigit Andhi Rahman (President University, 2017)
This paper discusses the development of institutions within international political economy over the course of the last 70 years. From World War II to the present, states have constructed regimes to manage some-but not all-aspects of the international economy. A once-strong regime to manage trade has weakened since the 1990s. Likewise, with the abandonment of dollar-gold convertibility in 1973, a robust regime to manage monetary relations collapsed. Conversely, states originally left finance unregulated but in 1988 created and progressively have strengthened rules to manage international banking. In production, the proposed Multilateral Agreement on Investment collapsed in 1998 without ever securing necessary multilateral support. Despite the variations, those institutions are the manifestation of the idea of embedded liberalism, a compromise between the need of developing a self-regulated market and providing economic security for the communities. Arguably, the development and variations in institutions are by and large shaped by the changes in international power structure and social purposes of the institutions. Furthermore, this paper also wants to address the prospect of embedded liberalism especially in the context of recent rise of populism and democratic rejection against free trade as reaction toward the results of globalization. It is too soon to argue about the end of embedded liberalism. This paper is structured into two main parts. The first part is a conceptual framework discussing the nature of institutions and its variations. It is mainly built from the work of John G. Ruggie on international institution. The second part is an empirical analysis of to what extent states are able to renew the promise of embedded liberalism in order to address citizens’ dissatisfaction with globalization and growing sense of political helplessness. This last section is indebted to Amitai Etzioni for developing communitarian solutions to populism.